(untitled) (Vietnam Journal of Community Medicine, 2025)
A cross-sectional descriptive study was conducted to determine some factors associated with dyslipidemia in elderly hypertensive patients. The study analyzed 180 medical records of elderly hypertensive patients who visited Nam Do General Clinic from January 2023 to October 2023.The results showed that individuals with a BMI ≥ 23 were 2.35 times more likely to have dyslipidemia compared to those with a BMI < 23 (OR=2.35, p=0.048, 95%CI=0.99-5.57). Additionally, the prevalence of dyslipidemia was higher in individuals with elevated blood pressure compared to those with normal current blood pressure levels (OR=0.224, p=0.032, 95%CI=0.51-0.98).No association was found between age, gender, occupation, living area, duration of hypertension, or hypertension complications and dyslipidemia in elderly hypertensive patients.